Molluscum contagiosum as a tattoo complication: a case report and literature review - Flávia Fenólio Nigro Marcelino; Jayme de Oliveira-Filho; Gabriela Machado Dias Junqueira; Márcia Ferraz Nogueira; Alexandre Ozores Michalany (Sociedade Brasileira de Dermatologia (SBD), 2021)
Tattooing is an ancient practice and very popular nowadays. The pigments used have changed over time but still present varied and poorly regulated compositions. There are many described cases of adverse effects after tattooing, mainly infectious and hypersensitivity reactions. We report the case of a 64-year-old woman, healthy, with papules on her eyebrows one month after performing micropigmentation. The excisional biopsy diagnosed molluscum contagiosum, and the lesions were curetted. There are few reports in the literature of the spread of molluscum contagiosum caused by tattooing.